Zen in Japanese art : - Hasumi, Toshimitsu (Philosophical Library, 1962)
Soon after its arrival in Japan, Zen Buddhism began to have a strong influence on the development of Japanese culture, and it eventually became part of Japan's spiritual and aesthetic foundation. Through the practice of various Japanese arts, many of the moral and spiritual values of Zen were taught and transmitted in Japan. During Japan's long periods of self-imposed isolation, art forms developed in ways that were specifically Japanese, and many of these art forms were strongly influenced by Zen Buddhism.